2020
DOI: 10.1021/acs.langmuir.0c01208
|View full text |Cite
|
Sign up to set email alerts
|

Cubic-like PtCuRu Nanocrystals with High Activity and Stability for Methanol Electro-oxidation

Abstract: Porous cubic-like PtCu and PtCuRu nanocrystals, which had a similar porous three-dimensional structure, were successfully prepared via the one-pot method. During the growth of the nanocrystals, cetyltrimethylammonium chloride and ascorbic acid were employed as the structure director and assistant reducing agent, respectively. The structure and possible formation of the nanocrystals were investigated. It is worth mentioning that the PtCuRu nanocrystals demonstrated a much better methanol electro-oxidation abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…To overcome these issues, Pt-based alloyed catalysts, including bimetallic alloy [PtM (M = Er, Pr, Ce, Dy, Tb, Nd, Ho, etc. ), Pt/MO 2 (M = Ce, Pr, Nd, and Sm), PtRh, , PtCu, , and PtNi , ], ternary alloy (PtFeCu, PtCuRu, PtCuBi, PtCuCo, and PtCuPd), and quaternary alloy (PtCuCoNi, PtCoNiMo, and PtRuFeCo) catalysts, were prepared. Particularly, catalysts mixed with CeO 2 have received wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these issues, Pt-based alloyed catalysts, including bimetallic alloy [PtM (M = Er, Pr, Ce, Dy, Tb, Nd, Ho, etc. ), Pt/MO 2 (M = Ce, Pr, Nd, and Sm), PtRh, , PtCu, , and PtNi , ], ternary alloy (PtFeCu, PtCuRu, PtCuBi, PtCuCo, and PtCuPd), and quaternary alloy (PtCuCoNi, PtCoNiMo, and PtRuFeCo) catalysts, were prepared. Particularly, catalysts mixed with CeO 2 have received wide attention.…”
Section: Introductionmentioning
confidence: 99%
“… Summary of MA and SA values in recent reported works for Pt‐based electrocatalysts with different composition and commercial Pt/C toward MOR. (1, [111] 2, [112] 3, [113] 4, [114] 5, [115] 6, [116] 7, [117] 8, [118] 9, [122] ). …”
Section: Advanced Strategies For High‐performance Aor Electrocatalystsmentioning
confidence: 99%
“…[24,105] To date, many elementals, such as Ni, Co, Fe, Cu, Au, Pd, Rh, Os, Ir, Ga, and so forth, have been introduced into Pt to form bior multi-metallic nanostructures. [24,46,47,99,[106][107][108][109][110][111][112][113][114][115][116][117][118] Figure 6 gives a summary of the MA and SA of Pt-based electrocatalysts with different compositions compared with commercial Pt/C, which illustrates that formation of alloy can remarkably enhance the electrocatalytic performance. Recently, Zhang's group modified the electronic structure of Pt through incorporating Ni into Pt.…”
Section: Composition Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Related reports have confirmed that the increase of heteroatomic interaction in ternary alloys was the reason for the significant improvement of catalytic activity. 29 Bai et al 30 synthesized the porous cubiclike PtCuRu nanocrystals by the one-pot method. The results displayed that the PtCuRu nanocrystals exhibited more excellent MOR ability and outstanding stability.…”
Section: ■ Introductionmentioning
confidence: 99%